24, EVALUATION OF THE POST-LIVER RESECTION EFFECTIVENESS OF SUBCOSTUME TAP BLOCK ANAGESIA COMBINED WITH PCA MORPHINE (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluation of postoperative pain relief efficacy of bilateral subcostal TAP block combined with PCA Morphine analgesia for liver resection compared with epidural analgesia.Subjects and methods: The study subjects included 60 patients with indications for liver resection surgery at Viet Duc University Hospital from January 2025 to June 2025. TAP group (group I): TAP block anesthesia under the lower ribs on both sides guided by ultrasound combined with PCA Morphine. Epidural group (group II): continuous infusion of epidural anesthesia. Evaluation of general characteristics: age, gender, BMI, ASA, anesthesia time, VAS cores at rest and during movement at time points 0.5; 3; 6; 12; 24; 30; 36; 48; 72 hours; changes in pulse, blood pressure and respiration.Results: Comparing the subcostal TAP block group combined with PCA Morphine (n = 30) and the epidural group (n = 30), the VAS pain scores at rest and during movement in the two groups were similar.Conclusion: The method of bilateral subcostal TAP block anesthesia combined with PCA Morphine analgesia for liver resection surgery compared with epidural analgesia has equivalent effectiveness.
Keywords: TAP block, epidural anesthesia, liver resection.